2015
DOI: 10.1002/app.42480
|View full text |Cite
|
Sign up to set email alerts
|

Current progress in the production of PLA–ZnO nanocomposites: Beneficial effects of chain extender addition on key properties

Abstract: Poly(lactic acid) (PLA) nanocomposites characterized by multifunctional end‐use properties are of high interest as new biosourced materials for the production of smart films, fibers, and injection‐molded components. In this work, PLA–ZnO nanocomposites designed for the extrusion of films were obtained by melt‐compounding PLA with up to 5 wt % ZnO rod‐like nanoparticles, nanofiller previously surface‐treated with a specific silane (triethoxycaprylylsilane). To improve the processing and performances of nanocomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
52
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 51 publications
(82 reference statements)
8
52
0
4
Order By: Relevance
“…On the other side, recent studies reveal that ZnO‐NPs and Zn compounds can degradate a series of polyesters and, specifically, PLA during melt compounding by various mechanisms. The proposed mechanism by Murariu et al is shown in Figure . In view of that, by adding the ZnO‐NPs to the PLA blend, the matrix‐located nanoparticles can cause the PLA to undergo a degradation, leading to the decrease of molecular weight and, consequently, viscosity reduction .…”
Section: Resultsmentioning
confidence: 99%
“…On the other side, recent studies reveal that ZnO‐NPs and Zn compounds can degradate a series of polyesters and, specifically, PLA during melt compounding by various mechanisms. The proposed mechanism by Murariu et al is shown in Figure . In view of that, by adding the ZnO‐NPs to the PLA blend, the matrix‐located nanoparticles can cause the PLA to undergo a degradation, leading to the decrease of molecular weight and, consequently, viscosity reduction .…”
Section: Resultsmentioning
confidence: 99%
“…[12][13][14] This chain extender is a multifunctional epoxy compound that can react with nucleophilic end groups -OH and -COOH of PLA, producing a polymer with high molecular weight. [16][17][18] The use of Joncryl in PLA was also reported for clay dispersion improvement in nanocomposites, [19] for blend compatibilization, [20] for an enhancement of PLA-ZnO nanocomposites properties, [21] and in polymerization of LA using a chain extender. [16][17][18] The use of Joncryl in PLA was also reported for clay dispersion improvement in nanocomposites, [19] for blend compatibilization, [20] for an enhancement of PLA-ZnO nanocomposites properties, [21] and in polymerization of LA using a chain extender.…”
Section: Introductionmentioning
confidence: 99%
“…Due also to low cost, ZnO particles (with sub-micro and nano-dimensions) are therefore ideal fillers for polymers to be applied in the field of active food packaging. Thus, ZnO particles have been incorporated into a number of different polymers used in food packaging [15,16], such as low-density polyethylene (LDPE) [17,18], isotactic polypropylene (iPP) [19][20][21][22][23][24], polyamide (PA) [18,25], and polylactic acid (PLA) [26].…”
Section: Introductionmentioning
confidence: 99%